Estudo da influência da progressão de carga na codigestão de dejeto suíno e cama de frango em reatores de mistura completa - Pereira Neto, Santiago (2018)
In this study, the influence of the load progression was evaluated, using poultry litter in reactors that had already been operating with swine waste, in relation to physical-chemical and operational parameters. In order to evaluate the solids content of the chicken litter, CSTR reactors were used with a useful volume of 12 L, the control reactor (R1) with only swine manure and the reactor for co-digestion swine and poultry litter (R2). It was possible to notice that the increase in methane productivity was up to 56% in the VOCs of 2.1 and 3.0 kgSV.m-3.d-1 based on the volatile solids (SV) of the chicken bed added. Average methane yield at R2 reached 0.54 LN CH4. Loor-1. d-1 for VOCs of 3.0 and 4.5 kgSV.m-3d-1. The values of AI/P and short-chain organic acids changed from 3.6-3 and 4.5 kgSV.m-3.d-1 (values close to 0.1 to 0.4), but the pH of the system remained stable due to the alkalinity of the swine manure. The total solids content (ST) at which the reactor was operated was 11.7% (m.v-1), during which time a large quantity of foam was formed in the system, which led to operational problems due to the reactor’s overload. In view of the limitation of many reactors operating with higher solids contents, CSTR is an important option for anaerobic co-digestion of a poultry litter and swine manure, two residues of relevant agroindustrial chains in Brazil and in the world.